EAR LEARNING MODEL: INOVASI PENDIDIKAN RESILIENSI BANJIR BERBASIS ADAPTASI SOSIAL DI SD PEMBANGUNAN LABORATORIUM UNP - Zahra Salsabillah Amanda; Ernawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to: 1) determine how flood resilience learning is implemented using the EAR Learning Model at SD Pembangunan Laboratorium UNP, 2) determine the effect of implementing the EAR Learning Model on improving students' understanding of flood resilience based on social adaptation at SD Pembangunan Laboratorium UNP, 3) determine how students apply social adaptation in flood-prone environments at SD Pembangunan Laboratorium UNP. This study used a quasi-experimental method with quantitative research and purposive sampling techniques, designating class V.B as the experimental class and class V.A as the control class. The data collection techniques used were observation, tests, documentation, and questionnaires. Flood resilience tests and questionnaires based on social adaptation were given to both classes after the treatment. The tests were given in the form of multiple-choice questions that had been tested for validity, reliability, and observation. The results showed that the implementation of flood resilience learning based on social adaptation used the EAR Learning Model with three syntaxes (Education, Adaptation, and Resilience). The post-test results of the experimental class students who used the EAR Learning Model were higher than those of the control class who used conventional methods. The average score of the experimental class was 77 and that of the control class was 63. Based on the results of the independent sample t-test, it is also known that the significance value is 0.000, which is smaller than 0.05, so H0 is rejected and Ha is accepted, and it can be concluded that the use of the EAR Learning Model has a positive effect on student learning outcomes on flood resilience material based on social adaptation. Based on the social adaptation questionnaire distributed to students in flood-prone areas, it was found that students at the UNP Laboratory Development Elementary School have a high level of social adaptation knowledge.